Thermally induced continuous water flow in long nanotube channels - Leng, Jiantao (2022)
Despite its importance for nanofluidic systems, achieving continuous water flow in long nanochannels remains a major challenge. Here, we propose a general principle to overcome this challenge by introducing a method that involves the building of a series of cascadable driving units, each unit carrying a net thermal gradient force, to maintain continuous water flow in an arbitrarily long nanochannel. Using molecular dynamics simulations and analytical modeling, we show that, within a single driving unit, the net thermal gradient force can be achieved through a multitude of strategies, including geometrical (e.g., a localized confinement), mechanical (e.g., a localized pinch), electrical (e.g., a point electric charge) and chemical (e.g., a point functionalization). The proposed method has fundamental significance for nanofluidic systems and potential applications in nanoscale mass transport and energy conversion devices.